2016
DOI: 10.5935/abc.20160005
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Remodeling: Concepts, Clinical Impact, Pathophysiological Mechanisms and Pharmacologic Treatment

Abstract: Cardiac remodeling is defined as a group of molecular, cellular and interstitial changes that manifest clinically as changes in size, mass, geometry and function of the heart after injury. The process results in poor prognosis because of its association with ventricular dysfunction and malignant arrhythmias. Here, we discuss the concepts and clinical implications of cardiac remodeling, and the pathophysiological role of different factors, including cell death, energy metabolism, oxidative stress, inflammation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
331
0
23

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 307 publications
(358 citation statements)
references
References 52 publications
4
331
0
23
Order By: Relevance
“…It should be emphasized that although the remodeling is an extremely complex event, after the infarction this process is clinically recognized by an increase in the LV cavity. In addition, a well-accepted concept is that the remodeling process is usually associated with deterioration of ventricular function [2][3][4][5]. Therefore, our study suggests that zinc administration attenuated infarct-induced ventricular remodeling, associated with improved systolic and diastolic function.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…It should be emphasized that although the remodeling is an extremely complex event, after the infarction this process is clinically recognized by an increase in the LV cavity. In addition, a well-accepted concept is that the remodeling process is usually associated with deterioration of ventricular function [2][3][4][5]. Therefore, our study suggests that zinc administration attenuated infarct-induced ventricular remodeling, associated with improved systolic and diastolic function.…”
Section: Discussionmentioning
confidence: 59%
“…In the acute phase, remodeling favors the formation of the aneurysm and predisposes the infarcted heart to ventricular rupture. Chronically, it is associated with a higher prevalence of malignant arrhythmias and ventricular dysfunction, as the noninfarcted region undergoes genetic, structural, and biochemical changes that will result in deterioration of the heart's functional capacity and death [1][2][3][4][5]. Therefore, strategies that attenuate remodeling result in improved postinfarction prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Our results demonstrated that RA, added to a normal rat chow diet, induced myocardial hypertrophy, as assessed by CSA. Regardless of the complexity of the remodeling process, it is well established that myocardium hypertrophy plays a key role on cardiac remodeling [28]. Interestingly, LV function was preserved with the treatment.…”
Section: Discussionmentioning
confidence: 91%
“…Transverse aortic constriction (TAC) in mice or rats is the most commonly used experimental method of modelling cardiac hypertrophy and fibrosis in animals . Currently employed treatments for patients with cardiac hypertrophy include calcium channel blockers, beta blockers, angiotensin‐converting enzyme inhibitors, angiotensin II receptor blockers, and diuretics …”
Section: Introductionmentioning
confidence: 99%